2005
DOI: 10.1017/s0033291704004118
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among patients with schizophrenia and reduced psychiatric hospital care

Abstract: Reduction of psychiatric beds did not generally increase the mortality of patients with schizophrenia. However, patients in their early years of illness experienced increased mortality after the steepest bed reduction. Improved recognition and treatment of somatic illness would benefit patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
66
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 19 publications
6
66
1
1
Order By: Relevance
“…The higher risk of mortality in males compared to females, especially in the first years after the onset of the disorder, might also contribute to explaining the finding of different incidences, although with comparable prevalence in the two sexes (Joukamaa et al, 2001;Heilä et al, 2005). Overall, sex differences among patients with schizophrenia include age of onset, symptoms severity at presentation, treatment response, course of illness and outcome (Grossman et al, 2006;Häfner, 2003;Tamminga, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The higher risk of mortality in males compared to females, especially in the first years after the onset of the disorder, might also contribute to explaining the finding of different incidences, although with comparable prevalence in the two sexes (Joukamaa et al, 2001;Heilä et al, 2005). Overall, sex differences among patients with schizophrenia include age of onset, symptoms severity at presentation, treatment response, course of illness and outcome (Grossman et al, 2006;Häfner, 2003;Tamminga, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…While suicide is usually associated with depression, the relative risk of death from suicide is increased nearly 10-fold in schizophrenia and 50-fold in anorexia nervosa. 8,9 What is perhaps most surprising in looking at morbidity and mortality data is that we have made so little progress on some of the most serious mental disorders. While we are seeing recent reductions in deaths from cardiac disease, AIDS, certain cancers, and even homicide, the mortality rate as measured by the number of suicides has changed little in the past century.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The risk is particularly high in the first episode of the illness and decreases with time after the first hospital admission. 5 Different studies, using different populations and methods, have yielded varying estimates of the suicide rate in schizophrenia. 6,7 While earlier research has suggested that up to 13% of patients with schizophrenia commit suicide, 2 more recent studies that take into account the variable suicide risk during the life span (a higher risk close to illness onset and thereafter a declining risk) have reported a lifetime suicide mortality of 4%-5%.…”
mentioning
confidence: 99%